Natural and directed antigenic drift of the H1 influenza virus hemagglutinin stalk domain. Issue 1 (December 2017) - Anderson, Christopher; Ortega, Sandra; Chaves, Francisco; Clark, Amelia; Yang, Hongmei; Topham, David; DeDiego, Marta
Abstract The induction of antibodies specific for the influenza HA protein stalk domain is being pursued as a universal strategy against influenza virus infections. However, little work has been done looking at natural or induced antigenic variability in this domain and the effects on viral fitness. We analyzed human H1 HA head and stalk domain sequences and found substantial variability in both, although variability was highest in the head region. Furthermore, using human immune sera from pandemic A/California/04/2009 immune subjects and mAbs specific for the stalk domain, viruses were selectedin vitro containing mutations in both domains that partially contributed to immune evasion. Recombinant viruses encoding amino acid changes in the HA stalk domain replicated wellin vitro, and viruses incorporating two of the stalk mutations retained pathogenicityin vivo . These findings demonstrate that the HA protein stalk domain can undergo limited drift under immune pressure and the viruses can retain fitness and virulencein vivo, findings which are important to consider in the context of vaccination targeting this domain.